695 Upregulated monocyte expression of PLIN2 is associated with plaque instability in coronary artery disease. (8th December 2021) - Canonico, Francesco; Severino, Anna; Camilli, Massimiliano; Migliaro, Stefano; Vinci, Ramona; Pidone, Chiara; Galli, Mattia; Pisano, Eugenia; Arcudi, Alessandra; Bonanni, Alice; Di Sario, Marianna; De Ciutiis, Astrid; et al.
Abstract: Aims: Perilipin 2 (PLIN2), a protein associated with intracellular lipid droplets (LDs), is involved in lipid metabolism of macrophages resident in atherosclerotic plaques and its up-regulation leads to LDs accumulation. LDs enlargement results in the macrophage transformation into foam cells, a key step for the onset of atherosclerosis. In the present study, we investigated the role of PLIN2 and its regulation mechanisms in atherosclerosis and plaque instability in patients with a diagnosis of ST-elevation myocardial infarction (STEMI) and stable chronic angina (SA). Methods and results: We enrolled 120 patients with a diagnosis of STEMI and 42 SA patients with symptoms of stable effort angina lasting more than 12 months. Peripheral blood mononuclear cells (PBMCs) were isolated from EDTA whole blood samples through standard gradient centrifugation over Ficoll-Hypaque. Monocytes were purified through indirect magnetic labelling of PBMCs. PLIN2 mRNA expression was investigated by Real Time-PCR and PLIN2 protein level was analysed in CD14 + monocytes by flow cytometry. Proteasome activity was assayed using AMC-tagged peptide substrate (Succ-LLVY-AMC), which releases free highly fluorescent AMC (Ex/Em 350/440 nm) in the presence of proteolytic activity. In CD14 + monocyte, PLIN2 protein expression was significantly increased in STEMI as compared to SA patients ( P  < 0.001), while PLIN2 mRNA level was not different in the two groups ( P  = n.s.). Despite proteasome activity was higher in STEMI as compared to SA patients ( P  < 0.001), significant inverse correlations were evident between PLIN2 levels and proteasome activity in the two groups ( P  = 0.05). Conclusions: CD14 + monocyte PLIN2 protein expression was higher in STEMI as compared to SA patients suggesting an involvement in plaque instability. Despite proteasome activity was higher in STEMI patients, probably due to the elevated inflammatory burden, PLIN2 could escape proteasome degradation in a more efficient manner in STEMI as compared to SA patients.